1998
DOI: 10.1159/000046497
|View full text |Cite
|
Sign up to set email alerts
|

Innervation Pattern of Different Cartilaginous Tissues in the Rat

Abstract: Background: The innervation of skeletal tissues by sensory nerves is poorly understood – especially of nerve fibres which reach into the bony and cartilaginous tissue. Methods: Samples of rat cartilaginous tissues from different locations (knee joint, vertebral column, temporomandibular joint) were fixed by perfusion and decalcified. The distribution of protein gene product (PGP) 9.5-, calcitonin gene-related peptide (CGRP)- and tachykinin (TK)-immunoreactive axons was analysed using fluorescence immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…In newborn rats, substance P and CGRP immunoreactive fibers were found in the knee perichondrium in close contact with chondrocytes (Oliva et al, 2005). Another study in rats demonstrated the presence of nerve fibers in different cartilaginous tissues, predominantly immunoreactive to CGRP (Schwab and Funk, 1998). Substance P and CGRP are involved in a variety of biological processes, such as maturation (Oliva et al, 2005), maintenance (Millward-Sadler et al, 2003), or repair of articular cartilage (Schwab and Funk, 1998).Their immuno-expression may also indicate the presence of sensory nerve fibers, which contribute to pain sensations (Suri et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In newborn rats, substance P and CGRP immunoreactive fibers were found in the knee perichondrium in close contact with chondrocytes (Oliva et al, 2005). Another study in rats demonstrated the presence of nerve fibers in different cartilaginous tissues, predominantly immunoreactive to CGRP (Schwab and Funk, 1998). Substance P and CGRP are involved in a variety of biological processes, such as maturation (Oliva et al, 2005), maintenance (Millward-Sadler et al, 2003), or repair of articular cartilage (Schwab and Funk, 1998).Their immuno-expression may also indicate the presence of sensory nerve fibers, which contribute to pain sensations (Suri et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although normal articular cartilage is not considered to be supplied with nerves, recent investigations showed nerve fibers in hyaline cartilage and fibrocartilage immunoreactive for calcitonin generelated peptide (CGRP) in rat pups (Schwab and Funk, 1998). Another study showed substance P and CGRP immunoreactive nerve fibers in perichondrium and in cartilage canals (Oliva et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidate neuromodulator for the chondrocyte's synthetic activity is the calcitonin-gene related peptide, but confirmative studies are lacking [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, sensory nerve fibers are observed in contact with a subpopulation of chondrocytes located in growth cartilage and at the surface of articular cartilage [13,14]. Calcitonin gene-related peptide (CGRP)-positive fibers, which originate from the periosteum and near insertion regions of muscle and tendons, innervate up to 25 μm into the articular and meniscal cartilage tissues in rat knee joints.…”
Section: Sensory and Sympathetic Nerve Fibers In Joint Physiologymentioning
confidence: 99%